Planejamento pedagógico como processo criativo na educação não formal em tecnologias e artes no Sesc São Paulo - Fujimori, Tatiana (2025)
The pedagogical planning in non-formal education is characterized by flexibility, as it does not follow rigid institutional guidelines. At Sesc São Paulo, particularly in the field of education in technologies and arts, there are no institutional documents that directly guide the pedagogical planning of activities. Consequently, each cultural venue, know in Portuguese as “Unidade Operacional”, whose team comprises educators and programming technicians, develops its own methodology, making it difficult to organize and evaluate the area globally. In light of this scenario, the main objective of this dissertation is to identify and develop planning tools that arise from subjective variables (programming teams and audiences) and objective variables (information flows and data) within the technology and arts program at Sesc São Paulo. The research adopts a qualitative approach, combining bibliographic, documentary, and empirical methods, with the analysis of internal meeting documents, master’s dissertations by educators from the program, and theoretical references on creativity and pedagogical planning. Drawing inspiration from the creative processes of the artistic and technological fields within the area, the investigation resulted in the construction of a planning model that values the subjectivities of the involved teams, while also identifying patterns that enable the creation of a database, assisting coordination in the systematization and monitoring of activities. Therefore, the study contributes to the improvement of pedagogical management in non-formal education, promoting a balance between creativity and methodological structuring